Non- governmental sources of agricultural extension in Kerala: status and potential - Simi George (Department of Agricultural Extension, College of Horticulture, 2005)
The study entitled “Non-governmental sources of agricultural extension in Kerala: Status and potential” was undertaken to “ collect and consolidate the different types of non-governmental extension sources involved in providing extension in the state; to classify the non-governmental extension sources based on their involvement in agricultural development; to analyse the activity focus, extension approaches followed and the mode of operation of the selected non-governmental extension agencies; to identify the success indicators of these non-governmental extension providers; and to analyse the salient personal and socio-economic characteristics of the beneficiaries under different agricultural programmes implemented by the non-governmental extension providers and to appraise the suggestions of the beneficiaries in improving the non-governmental extension services”. The study was carried out in five non-governmental extension agencies of Kerala, selected based on the predominant roles being performed by them, identified by the researcher. A sample of 30 beneficiaries covering different agricultural programmes was drawn from each agency following simple random sampling, thus making the total sample size 150. The personal and socio-economic characteristics of the beneficiary respondents as well as the probable success factors of the non-governmental extension agencies were selected through judges rating. The selected variables were measured using suitable procedures. Data were collected through pre-tested interview schedules and were analyzed and interpreted using appropriate statistical tools. Types of non-governmental extension agencies identified are: (1) Agricultural consultants/firms (2) Para technicians (3) Progressive farmers (4) Farmer’s organizations/Co-operatives (5) Non-Governmental Organizations (NGOs) (6) Agri-business firms (7) Input dealers (8) Print and electronic media (9) Private sector banks (10) Self-Help Groups (SHGs). The major roles found being performed by the non-governmental extension agencies are: (1) Advocacy (2) Consultancy (3) Infrastructure development (4) Input supply (5) Marketing. Mode of operation is influencing the outcome of non-governmental efforts. A high degree of concordance among beneficiaries regarding their perception about various success factors of the agencies was noticed. All the selected agencies were comparatively good in their effectiveness and the general factors found to be contributing to their effectiveness and success were communication methods, periodic evaluation and review of activities, co-ordination and integration of activities, resource use efficiency, participatory approach, and activities based on felt needs of clientele. Taking into account the effectiveness index computed for every selected agency, the agency selected for ‘marketing’ role came first and the agency selected for ‘consultancy’ role, the last. The factors that distinguished between the most effective and the least effective agencies were communication methods, periodic evaluation and review of activities and resource use efficiency. The mean status score was computed for assessing the status of any new agency that is to be taken up for studying on this particular aspect. Beneficiary respondents were analysed based on their socio-economic characteristics and 100 per cent variation could be noticed among them on their socio-economic characteristics. Regarding the scope for non-governmental extension services in future, both the staff and beneficiaries feel an ample scope for them in the coming years. Suggestions to improve the non-governmental extension services were collected after discussing with the beneficiary respondents. The study draws attention to the emergent need of effective utilization of the experiences and services of non-governmental extension agencies for rural development, particularly for agricultural development.